A multifunctional nanopipette for metal ion recognition and ultra-trace analysis. (11th April 2023) - Wang, Kang; Qian, Gongming; Li, Yunchuan; Wang, Ruixia; Guo, Jing
Abstract : A multifunctional nanopipette with a nanopore and a nanoelectrode is used for recognition of multiple metal ions and aM detection of Fe 3+ . Abstract : Nanopipette-based nanopore technologies have made significant progress for single molecule/nanoparticle/cell analysis. A multifunctional nanopipette with a nanopore and a nanoelectrode could improve the selectivity and sensitivity of traditional nanopipette-based nanopore sensing methods. In this work, multifunctional nanopipettes were developed for metal ion recognition and detection by combining the nanopore and electrochemical sensing methods. Both ionic and electrochemical currents were recorded for the recognition of multiple metal ions. Quantitative analysis shows that attomole level detection of Fe 3+ can be achieved. We demonstrate the real-time sensing of Fe 3+ with an error of concentration below 1.2%. We also show the renewable properties of the multifunctional nanopipette without the loss of performance. The research establishes a platform by integrating nanopore sensing and electrochemistry methods for ultra-trace chemical analysis with the advantages of portability and affordability.